NGHIÊN CỨU CHIẾT TÁCH DẦU TỪ SINH KHỐI VI TẢO HỌ BOTRYOCOCCUS SP LÀM NGUYÊN LIỆU CHO QUÁ TRÌNH TỔNG HỢP BIODIESEL - Thành, Nguyễn Trung; Toan, Nguyen Dang; Ngọ, Đinh Thị (Vietnam Journal of Science and Technology, 2015)
This study examines the effects of various solvents, temperature, and reaction time on oil extraction yield from microalgae Botryococcus sp biomass. Different solvents were used separately or in combination such as n-hexane, n-heptane, toluene, ethanol, iso-propanol, mixture of n-hexane/etanol and the mixture of n-heptane/iso-propanol. The results showed that with different conditions, the extraction yield was varied and the highest yield (37.36%) can be achived by using the solvent mixture of n-hexane/ethanol 2:1 (v/v) at temperature of 60ºC for 10h.